The Cerato-Platanin gene, rmcp, from Rigidoporus microporus was stably expressed during infection of Hevea brasiliensis - Wong, Mui Yun; Maiden, Nor Afiqah; Ahmad, Khairulmazmi; Syd Ali, Nusaibah; Atan, Safiah (Springer, 2024)
The rubber tree (Hevea brasiliensis) is vulnerable to infections by various fungal pathogens. White root disease infection is one of the most prevalent diseases of rubber in Malaysia. This disease is caused by the fungus Rigidoporus microporus. Delayed management of this disease can cause considerable reduction in total tree stand and ultimately decreased land productivity. The utilization of elicitor proteins to heighten host plant resistance represents a sustainable approach to disease control by reducing the use of chemical fungicides. The cerato-platanin protein family is the most widely reported class of elicitor proteins. This study isolated a member of the cerato-platanin family from R. microporus and evaluated its expression during H. brasiliensis infection. Total RNA was extracted from the mycelial sample of R. microporus followed by cDNA synthesis, isolation and cloning of the cerato-platanin transcript referred to as rmcp. In silico characterisation of the obtained sequence was then conducted and the relative expression of the gene was evaluated using RT-qPCR. A transcript of 438 bp encoding 145 amino acids protein, denoted as RmCP, was isolated and cloned. RmCP is composed of a ceratoplatanin domain and a predicted N-terminal signal peptide. Phylogenetic analysis grouped RmCP into a cluster together with cerato-platanin proteins originating from basidiomycetes. The expression of rmcp gene was consistent throughout the study period and was not significantly different from axenic culture. This suggests the gene to have a fundamental function in the life cycle of R. microporus.